Public Management - World Bank (World Bank, Washington, DC, 2012)
This Note on public management of pension funds concludes that publicly-managed pension reserves are often used to finance non-pension policy. Public pension fund managers tend to invest based on objectives unrelated to pension provision. These include social and economically target investments such as housing. Often governments look to pension reserves as a convenient and cheap way to finance deficits. One result is that public management produces poor returns relative to what could potentially be earned. Any pre-funding of long term pension obligations requires some minimal level of good governance. Although good governments perform better, public management produces inferior returns across all countries. As a result members of the scheme have to pay higher contributions or receive lower benefits. The evidence suggests that public management of pension reserves should generally be avoided.